2014
DOI: 10.1590/s1517-83822014005000043
|View full text |Cite
|
Sign up to set email alerts
|

Ochrobactrum anthropi bacteremia in a preterm infant with cystic fibrosis

Abstract: Ochrobactrum anthropi infection in newborn patients is rare, and the treatment is challenging because of its widespread and unpredictable resistance to antimicrobial agents and discrepancies between in vitro susceptibility and in vivo efficacy. We report the clinical and microbiological characteristics of Ochrobactrum anthropi bacteremia in a preterm patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The distribution of (pro)phages (represented by nodes) in the network allows for more precise insight into Ochrobactrum (pro)phages diversity. It was shown that 198 (70.5%) Ochrobactrum (pro)phages shared similarity to the phages infecting other Proteobacteria (223 (pro)phages in the network), which is representatives of the Terrabacteria group (54) or of phages recovered from the metagenomic samples for which hosts were not assigned (17). Amongst the Proteobacteria (pro)phages grouped together with Ochrobactrum phages, 89 viruses infected Alphaproteobacteria, 15 Betaproteobacteria, and 115 Gammaproteobacteria.…”
Section: Host Range Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of (pro)phages (represented by nodes) in the network allows for more precise insight into Ochrobactrum (pro)phages diversity. It was shown that 198 (70.5%) Ochrobactrum (pro)phages shared similarity to the phages infecting other Proteobacteria (223 (pro)phages in the network), which is representatives of the Terrabacteria group (54) or of phages recovered from the metagenomic samples for which hosts were not assigned (17). Amongst the Proteobacteria (pro)phages grouped together with Ochrobactrum phages, 89 viruses infected Alphaproteobacteria, 15 Betaproteobacteria, and 115 Gammaproteobacteria.…”
Section: Host Range Analysismentioning
confidence: 99%
“…In these cases, bacteria are isolated mostly from immunocompromised patients, as pathogens colonizing respiratory tract and wounds. These are mostly opportunistic infections, including central venous catheter-associated bloodstream infections, prosthetic valve endocarditis, septic arthritis, osteomyelitis, and peritonitis [16][17][18][19][20]. Hence, to prevent using pathogenic or multi-resistant strains, the application of Ochrobactrum spp.…”
Section: Introductionmentioning
confidence: 99%
“…sociated with the presence of central device. The identification of the microorganism was initially by automated method (BATEC system), with subsequent use of MALDI-TOF, PCR, and genetic sequencing of 16S ribosomal RNA [16].…”
Section: Discussionmentioning
confidence: 99%
“…Ochrobactrum anthropi is an emerging opportunistic pathogen [ 1 , 2 ] that has typically been associated with bacteremia and sepsis in immunocompromised patients and in patients with indwelling medical devices [ 3 , 4 ]. However, with improved speciation techniques, O. anthropi has now been implicated in a broad range of infections, even in immunocompetent hosts.…”
Section: Introductionmentioning
confidence: 99%